Melatonin treatment protects against sepsis-induced functional and biochemical changes in rat ileum and urinary bladder - ŞENER, GÖKSEL; ELÇİOĞLU, HATİCE KÜBRA (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Sepsis is commonly associated with enhanced generation of reactive oxygen metabolites, which lead to multiple organ dysfunction. The aim of this study was to examine the role of melatonin, a potent antioxidant, in protecting the intestinal and bladder tissues against damage in a rat model of sepsis. Sepsis was induced by cecal ligation and perforation (CLP) in Wistar Albino rats. Sham operated (control) and CLP group received saline or melatonin (10 mg/kg, ip) 30 minutes prior to and 6 hours after the operation. Sixteen hours after the surgery, rats were decapitated and the intestinal and urinary bladder tissues were used for contractility studies, or stored for the measurement of malondialdehyde (MDA) content -an index of lipid peroxidation-, glutathione (GSH) levels -a key antioxidant- and myeloperoxidase (MPO) activity- an index of neutrophil infiltration-. Heal and bladder MDA levels in the CLP group were significantly increased (p < 0.001) with concomitant decreases in GSH levels (p < 0.01 -p < 0.001) when compared to the control group. Similarly, MPO activity was significantly increased (p < 0.001) in both ileum and bladder tissues. On the other hand, melatonin treatment significantly reversed (p < 0.001) the elevations in MDA and MPO levels, while reduced GSH levels were increased back to the control levels (p < 0.01-p < 0.001). In the CLP group, the contractility of the ileal and bladder tissues decreased significantly compared with controls. Melatonin treatment of the CLP group restored these responses. In this study, CLP induced dysfunction of the ileal and bladder tissue of rats was reversed by melatonin treatment. Moreover, melatonin, as an antioxidant, abolished the elevation in lipid peroxidation products and myeloperoxidase activity, and reduction in the endogenous antioxidant glutathione and thus protected the tissues against sepsis-induced oxidative damage. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: sepsis; melatonin; oxidative damage; intestine; urinary bladder; LIPID-PEROXIDATION; MYELOPEROXIDASE ACTIVITY; REACTIVE OXYGEN; FREE-RADICALS; INFLAMMATION; INJURY; GLUTATHIONE; DYSFUNCTION; MODELS; TISSUE